Dietary Intake of Total Carbohydrates, Sugar and Sugar-Sweetened Beverages, and Risk of Inflammatory Bowel Disease: A Systematic Review and Meta-Analysis of Prospective Cohort Studies - Khademi, Zeinab; Milajerdi, Alireza; Larijani, Bagher; Esmaillzadeh, Ahmad (Frontiers in Nutrition, 2021)
Objectives: No earlier study has summarized findings from prospective cohort studies on the association of dietary carbohydrates, sugar and sugar-sweetened beverages (SSB) and risk of Inflammatory Bowel Disease (IBD). The current study was done to quantitatively summarize earlier information from prospective cohort studies on the link between dietary carbohydrate intake, sugar and SSB intake with risk of IBD. Methods: We searched for relevant studies published up to January 2020 through PubMed, Medline, SCOPUS, EMBASE, and Google Scholar with the use of relevant keywords. All prospective cohort studies investigating the association of dietary carbohydrate intake, sugar and SSB consumption with risk of IBD were included. Results: Combining 5 effect sizes from 4 cohort studies, we found no significant association between dietary intake of carbohydrates and risk of Ulcerative Colitis (UC) (Pooled RR: 1.22; 95% CI: 0.70 to 2.14). The same findings were obtained for risk of Crohn’s Disease (CD) (1.06; 0.64 to 1.75) based on 4 studies with 5 effect sizes. We observed a significant positive association between sugar intake and risk of UC (1.59; 1.15 to 2.20) as well as CD (RR: 1.90; 95% CI: 1.06 to 3.41) when we combined 5 effect sizes from 4 cohort studies. The overall effect size, based on four estimates, revealed no significant association between SSBs consumption and risk of UC (RR: 1.02; 95% CI: 0.92 to 1.12) and CD (RR: 1.22; 95% CI: 0.91 to 1.64). Conclusions: Summarizing earlier studies, we found that sugar intake was associated with increased risk of IBD and its subtypes. We failed to find any significant association between dietary intake of carbohydrates and SSBs consumption and risk of IBD and its subtypes.